MARKETING STRATEGIES TO IMPROVE ROOM OCCUPATION IN THE NEW NORMAL ERA OF THE COVID-19 PANDEMIC AT THE PAYOGAN RESORT and SPA KEDEWATAN UBUD GIANYAR - Kurniawati, Nuning; Bayu Wisnawa, I Made; Rusmiati, Ni Nyoman (Akademi Komunitas MAPINDO, 2022)
This study analyses the marketing strategy in increasing room occupancy in the new normal era of the covid-19 pandemic at The Payogan Villa Resort and Spa Kedewatan, Ubud, Gianyar. The objectives of this paper are: (i) To find out the strengths, weaknesses, opportunities, and threats of The Payogan Villa Resort and Spa, Ubud, Gianyar. (ii) To determine the marketing strategy for increasing room occupancy in the New Normal Era of the Covid-19 Pandemic At The Payogan Villa Resort and Spa, Ubud, Gianyar. The analysis technique used is descriptive qualitative and SWOT. The results of the study indicate that (i) Strengths lie in a very strategic location, facilities and competitive room rates; Weaknesses in promotion efforts that have not been maximized, slow service, poor employee appearance; Opportunities for the existence of domestic tourists, public trust and government support; The threats faced are that there is no certainty over the end of the pandemic and competitors; (ii) The marketing strategy is carried out by improving e-marketing and developing distribution channels as well as the competence of hotel employees. Keywords : Marketing Strategy, Increasing Room Occupancy, New Normal Era Covid-19 Pandemic